Organic Farming Innovation: Building Public Awareness of the Health and Environmental Benefits of Organic Farming - Dadang Muhammad Hasyim; Patriandi Nuswantoro; Syamsu Rijal; Syamsul Anwar; Azhariah Rachman (PT. Global Research Collaboration, 2025)
Farmers in Kelompok Tani Sukawargi 2, Sukawargi Village, Cisurupan District, Garut Regency face challenges related to their dependence on conventional farming that uses chemicals, which impact health and environmental sustainability. A community service program was then implemented to enhance the knowledge, skills, and awareness of the community regarding the benefits of organic farming. The training provided covered the basic principles of organic farming, organic fertilizer production, natural soil management, and pest control using natural ingredients. The training also educated farmers on the importance of transitioning from chemical-based farming to organic farming for the sake of health and environmental sustainability. The results of the community service showed a significant improvement in farmers' understanding of organic farming and organic product marketing. Farmers showed a high interest in applying the techniques learned and implementing broader product marketing strategies. Awareness of the impact of chemicals on health and the environment also increased. Furthermore, training on organic product marketing opened up better economic opportunities for farmers.